Call for Papers - Detection of Intrusions & Malware and Vulnerability Assessment (DIMVA 2006) - Büschkes, Roland; Heuse, Marc; Laskov, Pavel (Technische Universität Dortmund, 2007)
The special interest group Security - Intrusion Detection and Response (SIDAR) of the German Informatics Society (GI) organizes DIMVA as an annual conference that brings together experts from throughout and outside of Europe to discuss the state of the art in the areas of intrusion detection, malware detection, and vulnerability assessment.
Third GI SIG SIDAR Conference on Detection of Intrusions & Malware, and Vulnerability Assessment
Keywords: 004